2016
DOI: 10.1186/s12909-016-0695-0
|View full text |Cite
|
Sign up to set email alerts
|

Compassion training in healthcare: what are patients’ perspectives on training healthcare providers?

Abstract: BackgroundThe purpose of this qualitative study was to investigate advanced cancer patients’ perspectives on the importance, feasibility, teaching methods, and issues associated with training healthcare providers in compassionate care.MethodsThis study utilized grounded theory, a qualitative research method, to develop an empirical understanding of compassion education rooted in direct patient reports. Audio-recorded semi-structured interviews were conducted to obtain an in-depth understanding of compassion tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 42 publications
2
76
0
1
Order By: Relevance
“…The women in this investigation discussed opposing styles of communication, and they identified that “feeling supported” during their interactions with health professionals resulted in a positive experience. This is supported by previous studies in cancer communication indicating that patients not only value adequate information to assist them in making informed decisions about their care (Chan, Kan, Lee, Chan, & Lam, 2012) but also communication styles that demonstrate patient‐centeredness and value patients as worthy and active participants in their care (Sinclair et al, 2016; Skea, Maclennan, Entwistle, & N'Dow, 2014; Zucca, Sanson‐Fisher, Waller, & Carey, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…The women in this investigation discussed opposing styles of communication, and they identified that “feeling supported” during their interactions with health professionals resulted in a positive experience. This is supported by previous studies in cancer communication indicating that patients not only value adequate information to assist them in making informed decisions about their care (Chan, Kan, Lee, Chan, & Lam, 2012) but also communication styles that demonstrate patient‐centeredness and value patients as worthy and active participants in their care (Sinclair et al, 2016; Skea, Maclennan, Entwistle, & N'Dow, 2014; Zucca, Sanson‐Fisher, Waller, & Carey, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Data were collected from the participants using focus groups and one‐on‐one semistructured interviews. An interview guide (Table ) was used for the focus groups and was developed based on our literature reviews (Sinclair, Kondejewski, Raffin‐Bouchal, King‐Shier, & Singh, ; Sinclair, Raffin‐Bouchal, Venturato, Mijovic‐Kondejewski, & Smith‐MacDonald, ; Sinclair, Russell, Hack, Kondejewski, & Sawatzky, ; Sinclair, Norris, et al., ) and the research team's previous experience in conducting qualitative studies (Sinclair, Bouchal, Chochinov, Hagen, & McClement, ; Sinclair, McClement, et al., ; Sinclair, Torres, et al., ; Sinclair, Beamer, et al., ). While the guiding questions were designed to facilitate conversations, including potential barriers and facilitators, two targeted questions were developed to address this topic specifically: What do you feel are the major influencers of compassionate care in your practice?…”
Section: Methodsmentioning
confidence: 99%
“…37-38). When surveyed, patients themselves are unsurprisingly enthusiastic about compassion training for healthcare providers (Sinclair, Torres, Raffin-Bouchal, Hack, McClement, Hagen and Chochinov, 2016).…”
Section: Graduate Studentsmentioning
confidence: 99%